BANTUAN KEPADA SEKOLAH AGAMA RAKYAT, SATU KAJIAN SEJARAH DAN TUJUAN ASAL - Umar, Azizi (Journal of Al-Tamaddun, 2007)
This article discusses the history of the development of Sekolah Agama Rakyat and the aids given by the government to such a school such as a student?s opportunity to sit for the national examinations, financial aids per capita etc. It will also talk about the take-over of such schools by the government and the absorption of their teachers to the government schools.